Selfies : searching for the image of God in a digital age - Detweiler, Craig, 1964- (Grand Rapids, Michigan : Brazos Press, a division of Baker Publishing Group, 2018)
Selfies are ubiquitous. They can be silly or serious, casual or curated. Within moments, smart phone users can capture their image and post it across multiple social media platforms to a global audience. But do we truly understand the power of image in our image-saturated age? How can we seek God and care for each other in digital spaces? Craig Detweiler, a nationally known writer and speaker and an avid social media user, examines the selfie phenomenon, placing selfies within the long history of self-portraits in art, literature, and photography. He shows how self-portraits change our perspective of ourselves and each other in family dynamics, education, and discipleship. Challenging us to push past unhealthy obsessions with beauty, wealth, and fame, Detweiler helps us to develop a thoughtful, biblical perspective on selfies and social media and to put ourselves in proper relation to God and each other. He also explains the implications of social media for an emerging generation, making this book a useful conversation starter in homes, churches, and classrooms. Each chapter ends with discussion questions and a photo assignment for creating a selfie in response to the chapter.
How do you solve a problem like the selfie? -- Reflected beauty: the ancient self -- Mastering the mirror: a renaissance of the self -- Reframing memories: the literary self -- Seizing the light: photographing ourselves -- Behind the mask: the psychological self -- Instapressure: the selfie today -- Augmented and transfigured: the selfie tomorrow.
Includes bibliographical references and index.
Keywords: Self -- Religious aspects -- Christianity; Social media -- Religious aspects -- Christianity; Self-portraits.